Student Competency Analysis Based on 2013 Curriculum Implementation - Rahayu, Eva Nur; Rozi, Fahrur (Economic Education Analysis Journal, 2021)
This study aimed to analyze and illustrate how high the student’s competency is from the aspects of attitude competence, knowledge competence and skill competence in the implementation of curriculum 2013. The population of this study were 63 students of class XII under the major of Office Automation and Management at SMK Teuku Umar Semarang. The sampling technique used census sample. Data collection techniques used in this study were observation, interview, questionnaire, and documentation. This study used descriptive analysis with index number. The results of this study showed that the overall student competence had 78.97% of an average total index. Meanwhile, the partial index indicated that the competence of attitude got 80.63%. Knowledge competence got 76.85%. Skill Competence got 79.42%. The conclusion of this research can be drawn that the student’s competence on attitude aspect, knowledge, and skill competency as a whole had reached high criteria average. Suggestions on this study are 1) the teachers are encouraged to give appreciation to students who are active in class, 2) the teacher should promote the values of character values in the students during learning activities, 3) teachers and students should help each other develop the student’s skills